2021
DOI: 10.7554/elife.65108
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin preserves metabolic fitness during aging

Abstract: Adiponectin is essential for the regulation of tissue substrate utilization and systemic insulin sensitivity. Clinical studies have suggested a positive association of circulating adiponectin with healthspan and lifespan. However, the direct effects of adiponectin on promoting healthspan and lifespan remain unexplored. Here, we are using an adiponectin null mouse and a transgenic adiponectin overexpression model. We directly assessed the effects of circulating adiponectin on the aging process and found that ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 56 publications
4
40
0
Order By: Relevance
“…Adiponectin is an adipose-derived peptide hormone that activates lipid utilization and mitochondrial oxidative pathways in target tissues 22 , 23 . Adiponectin has been linked to metabolic dysfunction associated with obesity 24 , 25 and aging 26 , 27 , and has been implicated in the mechanisms of delayed aging by caloric restriction 28 , 29 . Adiponectin circulates as a multimer and the high molecular weight (HMW) isoform has been specifically linked to insulin sensitivity 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Adiponectin is an adipose-derived peptide hormone that activates lipid utilization and mitochondrial oxidative pathways in target tissues 22 , 23 . Adiponectin has been linked to metabolic dysfunction associated with obesity 24 , 25 and aging 26 , 27 , and has been implicated in the mechanisms of delayed aging by caloric restriction 28 , 29 . Adiponectin circulates as a multimer and the high molecular weight (HMW) isoform has been specifically linked to insulin sensitivity 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Circulating adiponectin concentrations appear to be decreased even further (Figure 1 - figure supplement 2D-2F), perhaps suggesting that flux of translated adiponectin protein is impaired through the secretion pathway. Of note, hypoadiponectinemia is associated with insulin resistance (Cook & Semple, 2010; N. Li et al, 2021), with discrepant reports on osteogenesis (Lewis, Edwards, Naylor, & McGettrick, 2021). Thus, we evaluated systemic metabolism in BMAd-Cre mice and found that body weight, glucose tolerance, WAT depot weights, and tibial trabecular and cortical bone variables are unaffected by this degree of hypoadiponectinemia (Figure 1 - figure supplement 2G-2P).…”
Section: Resultsmentioning
confidence: 99%
“…For two of the three proteins that were decreased in T2D compared to controls, our findings here are in accord with the findings reported in IGT, where adiponectin and endocan were two of the top differentially expressed proteins that were found to be decreased in those with IGT and reduced β-cell sensitivity [ 15 ]. Low adiponectin levels have previously been linked to insulin resistance and β-cell function [ 24 , 25 , 26 ]; adiponectin levels are inversely correlated with body fat and have been purported to be a biomarker of adipose tissue health [ 4 , 27 , 28 ]. Endocan is a proteoglycan expressed in endothelial cells and adipocytes and low levels are associated with inflammation and visceral obesity [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%